Structure and kinematics of molecular disks in fast-rotator early-type galaxies - Young, L; Bureau, M; Cappellari, M (Institute of Physics Publishing, 2008)
We present interferometru; observations resolving the CO emission in the four gas-rich lenticular galaxies NGC 3 032, NGC 4150, NGC 4459, and NGC 4526, and we compare the CO distribution and kinematics to those of the stars and ionized gas. Counterrotation documents an external origin for the gas in at least one case (NGC 3032), and the comparisons to stellar and ionized gas substructures in all four galaxies offer insights into their formation histories. The molecular gas is found in kpc-scale disks with mostly regular kinematics and average surface densities of 100-200 M⊙ pc -2. The disks are well aligned with the stellar photometric and kinematic axes. In the two more luminous Virgo Cluster members NGC 4459 and NGC 4526 the molecular gas shows excellent agreement with circular velocities derived independently from detailed modeling of stellar kinematic data. There are also two puzzling instances of disagreements between stellar kinematics and gas kinematics on subkiloparsec scales. In the inner arcseconds of NGC 3032 the CO velocities are significantly lower than the inferred circular velocities, and the reasons may possibly be related to the external origin of the gas but are not well understood. In addition, the very young population of stars in the core of NGC 4150 appears to have the opposite sense of rotation from the molecular gas. © 2008. The American Astronomical Society. All rights reserved.